2000
DOI: 10.1007/s002689910048
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Complicated Duodenal Ulcers: Controlled Trials

Abstract: Indications for surgery of duodenal ulcer (DU) have changed radically because of the efficacy of H(2)-antagonists, endoscopic procedures, and eradication of Helicobacter pylorus. The aim of this study was to analyze the current literature to determine if definitive surgery is still relevant for complicated DU (bleeding, perforation, gastric outlet obstruction). Two studies have compared early to late surgery in terms of bleeding. One recommended early surgery (significant reduction in mortality) in the elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
10

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 64 publications
0
36
0
10
Order By: Relevance
“…As soon as the diagnosis is made, resuscitative measures like nasogastric tube aspiration, fluid resuscitation, PPI administration and antimicrobial therapy should be started. In our study, under general anaesthesia, laparatomies were done with simple closures of the perforations by using vicryl 2-0, omental patches were fixed around the perforations, thorough claim that the prognosis is not related to the surgical procedure itself [11,12].The present study showed that the risk of mortality and morbidity was statistically significant when the patient was submitted to surgery with a perforation time which was later than 24 hours , which was in agreement with the reports in the literature, which emphasized on the importance of early surgical interventions in improving the outcomes [13]. The increase in the therapeutic delay was mainly due to a delayed access to the hospital, since the patients were treated immediately after their admissions .It has been shown that the therapeutic delay increases the mortality rate [14].…”
Section: Methodsmentioning
confidence: 99%
“…As soon as the diagnosis is made, resuscitative measures like nasogastric tube aspiration, fluid resuscitation, PPI administration and antimicrobial therapy should be started. In our study, under general anaesthesia, laparatomies were done with simple closures of the perforations by using vicryl 2-0, omental patches were fixed around the perforations, thorough claim that the prognosis is not related to the surgical procedure itself [11,12].The present study showed that the risk of mortality and morbidity was statistically significant when the patient was submitted to surgery with a perforation time which was later than 24 hours , which was in agreement with the reports in the literature, which emphasized on the importance of early surgical interventions in improving the outcomes [13]. The increase in the therapeutic delay was mainly due to a delayed access to the hospital, since the patients were treated immediately after their admissions .It has been shown that the therapeutic delay increases the mortality rate [14].…”
Section: Methodsmentioning
confidence: 99%
“…Для электрофизиологической оценки состоя ния МЭФ желудка и кишечника использовали ме тод ПЭГЭГ, которую выполняли аппаратом ГастросканГЭМ по стандартной методике [11,16].…”
Section: материал и методыunclassified
“…Пациен тов, подлежащих оперативному лечению, наиболее часто объединяют в группу субкомпенсированного ПДС, что приводит к существенному различию при водимых разными авторами результатов его хирур гического лечения [1,3,5,6,8,11].…”
unclassified
“…Contudo, sabe-se que a instabilidade hemodinâmica e anemia são fatores relacionados a complicações e maior letalidade nos doentes operados por úlcera péptica hemorrágica [10][11][12] . Portanto, postergar a indicação de uma operação pode determinar pior prognóstico.…”
Section: Introductionunclassified
“…Outras variáveis também são analisadas para a indicação precisa do tratamento operatório, como idade, local e características endoscópicas das úlceras, histó-ria prévia de utilização de fármacos antiinflamatórios não esteróides, doença péptica crô-nica, tipo sangüíneo e volume de concentrados de hemácias transfundido 9 . Esta variedade de fatores muitas vezes torna difícil a decisão quanto à melhor forma de tratamento.Contudo, sabe-se que a instabilidade hemodinâmica e anemia são fatores relacionados a complicações e maior letalidade nos doentes operados por úlcera péptica hemorrágica [10][11][12] . Portanto, postergar a indicação de uma operação pode determinar pior prognóstico.…”
unclassified